2020
DOI: 10.3847/1538-4357/ab67b8
|View full text |Cite
|
Sign up to set email alerts
|

Searching for z > 6.5 Analogs Near the Peak of Cosmic Star Formation

Abstract: Strong [O III]λλ4959,5007+Hβ emission appears to be typical in star-forming galaxies at z>6.5. As likely contributors to cosmic reionization, these galaxies and the physical conditions within them are of great interest. At z>6.5, where Lyα is greatly attenuated by the intergalactic medium, rest-UV metal emission lines provide an alternative measure of redshift and constraints on the physical properties of star-forming regions and massive stars. We present the first statistical sample of rest-UV line meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 97 publications
11
62
0
Order By: Relevance
“…The emerging picture from extensive work at both z ∼ 2 − 4 (e.g. Nakajima et al 2018;Mainali et al 2019;Du et al 2020) and in the local z ∼ 0 Universe (e.g. Rigby et al 2015;Senchyna et al 2017Senchyna et al , 2019 suggests that such prominent C iii] emission requires a combination of both very high specific star formation rates 10 − 100Gyr −1 and very metal-poor (Z/Z 0.2, 12+log O/H 8.0) stars and gas.…”
Section: Nebular C Iii] Emission Powered By Moderately Metal-poor Massive Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging picture from extensive work at both z ∼ 2 − 4 (e.g. Nakajima et al 2018;Mainali et al 2019;Du et al 2020) and in the local z ∼ 0 Universe (e.g. Rigby et al 2015;Senchyna et al 2017Senchyna et al , 2019 suggests that such prominent C iii] emission requires a combination of both very high specific star formation rates 10 − 100Gyr −1 and very metal-poor (Z/Z 0.2, 12+log O/H 8.0) stars and gas.…”
Section: Nebular C Iii] Emission Powered By Moderately Metal-poor Massive Starsmentioning
confidence: 99%
“…These data have revealed surprisingly prominent emission from doubly-and triply-ionized carbon in the rest-UV of several intrinsically-luminous or gravitationally lensed systems at z > 6 (Stark et al 2015a,b;Mainali et al 2017;Schmidt et al 2017;Hutchison et al 2019). While emission in C iii] λλ1907, 1909 (hereafter C iii]) at such high equivalent widths ( 15 Å) is rare in typical massive galaxies at lower redshifts (Du et al 2017), a growing body of work at z ∼ 2 with VI-MOS and MUSE and in the local Universe ( 100 Mpc) with the Cosmic Origins Spectrograph onboard the Hubble Space Telescope (HST /COS) has revealed that this semi-forbidden doublet is routinely detected in subsolar metallicity galaxies at very high sSFR (Rigby et al 2015;Maseda et al 2017;Senchyna et al 2017;Nakajima et al 2018;Du et al 2020). However, even the latest stellar population synthesis models struggle to reproduce the highest equivalent width emission in C iii] detected at z ∼ 2-6.…”
Section: Introductionmentioning
confidence: 99%
“…This technique uses follow-up spectroscopic observations, targeting high-z candidate galaxies, to measure the strength of Lyα emission from galaxies in the reionization era. Initial studies using Lyα spectroscopy have found an apparent deficit of Lyα emission at z > 6.5 (e.g., Fontana et al 2010;Pentericci et al 2011;Finkelstein et al 2013;Pentericci et al 2014;Caruana et al 2012Caruana et al , 2014Curtis-Lake et al 2012;Mallery et al 2012;Ono et al 2012;Schenker et al 2012Schenker et al , 2014Treu et al 2012Treu et al , 2013Tilvi et al 2014;Vanzella et al 2014;Schmidt et al 2016;De Barros et al 2017;Fuller et al 2020), implying an increasing H I fraction in the IGM from z ∼ 6 → 7, although other Lyα systematics with galaxy evolutionary features are a factor in these measurements (e.g., Finkelstein et al 2012b;Yang et al 2017;Tang et al 2019;Trainor et al 2019;Du et al 2020;Hassan & Gronke 2021;Weiss et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, multi-object spectroscopic observations with large ground-based telescopes (e.g., Keck/DEIMOS, Keck/MOSFIRE, VLT/FORS2, VLT/KMOS, VLT/MUSE) have delivered a number of confirmed Lyα emitters at/around the end of reionization (e.g., Finkelstein et al 2013;Schenker et al 2014;Tilvi et al 2014;Oesch et al 2015;Zitrin et al 2015;Song et al 2016a;Herenz et al 2017;Hoag et al 2017;Laporte et al 2017;Stark et al 2017;Jung et al 2018Jung et al , 2019Pentericci et al 2018a;Mason et al 2019;Khusanova et al 2020). Initial studies of the simple "Lyα fraction" (= N LAE /N LBG ), where N LAE is the number of Lyα-detected objects and N LBG is the number of high-z candidate galaxies observed in spectroscopic observations, have found an apparent deficit of Lyα emission at z > 6.5 (e.g., Fontana et al 2010;Pentericci et al 2011Pentericci et al , 2018a, implying an increasing H I fraction in the IGM from z ∼ 6 → 7, although other Lyα systematics with galaxy evolutionary features need to be taken into account (e.g., Yang et al 2017a;Du et al 2020;Tang et al 2019;Trainor et al 2019).…”
Section: Introductionmentioning
confidence: 99%